Pengembangan Media Pembelajaran Boardgame Matematika Kelas XI Dengan Materi Matriks Di SMA Negeri 105 Jakarta - Desy Henika Putri Butar-Butar; Ilmi Arifiyah; Mella Novallina (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
Board games are one of the learning media to increase student interest in a subject. And on this occasion I made "Domino Match". And to determine the material to be applied I did it to a high school (SMA). Based on interviews with two material experts at the school, I know that the material is quite difficult for the students there, namely the Matrix. So I apply the matrix material to a game in the form of domoni cards, with the hope that their interest will arise and their perspective on Mathematics. The selection of game tools in the learning process can be adjusted to the characteristics and needs of these students. Then in designing or making a game tool in general based on criteria that are in accordance with the cognitive development of students. Based on the results of the research there are 4 (four) factors that affect the low student learning outcomes, namely, the lack of student interest in mathematics, lack of student concentration during the process learning, low understanding of student concepts, and lack of student discipline.